2015
DOI: 10.18632/oncotarget.4491
|View full text |Cite
|
Sign up to set email alerts
|

Inverse expression of somatostatin and CXCR4 chemokine receptors in gastroenteropancreatic neuroendocrine neoplasms of different malignancy

Abstract: IntroductionSomatostatin receptors (SSTR) are widely distributed in well-differentiated neuroendocrine neoplasms (NEN) and serve as primary targets for diagnostics and treatment. An overexpression of the chemokine receptor CXCR4, in contrast, is considered to be present mainly in highly proliferative and advanced tumors. Comparative data are still lacking, however, for neuroendocrine carcinomas (NEC).MethodsSSTR subtype (1, 2A, 3, 5) and CXCR4 expression was evaluated in G1 (n = 31), G2 (n = 47), and low (G3a;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
67
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 54 publications
9
67
1
Order By: Relevance
“…SSTR-2a is believed to be an indicator of welldifferentiated morphology, and the discriminative significance of the surrogate marker SSTR-2a and p53 have recently been studied in pancreatic NEN with a Ki67index > 20% [7]. We found that SSTR-2a expression is not restricted to well-differentiated tumours as it was detected as strongly positive in 26% and heterogeneously positive in 12% of the poorly differentiated GEP-NEN, which is confirmed by various studies [7,12,14,32]. The presence of somatostatin receptors makes these neuroendocrine neoplasms potentially amenable to treatment with PRRT in selected patients with high uptake on Adjusted for age (> 65 years), gender, grade of differentiation (well-vs. poorly differentiated), primary tumour (pancreas vs. other primary tumours), tumour burden (locoregional disease vs. disseminated), performance status (PS > 2), and treatment (surgery or chemotherapy).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…SSTR-2a is believed to be an indicator of welldifferentiated morphology, and the discriminative significance of the surrogate marker SSTR-2a and p53 have recently been studied in pancreatic NEN with a Ki67index > 20% [7]. We found that SSTR-2a expression is not restricted to well-differentiated tumours as it was detected as strongly positive in 26% and heterogeneously positive in 12% of the poorly differentiated GEP-NEN, which is confirmed by various studies [7,12,14,32]. The presence of somatostatin receptors makes these neuroendocrine neoplasms potentially amenable to treatment with PRRT in selected patients with high uptake on Adjusted for age (> 65 years), gender, grade of differentiation (well-vs. poorly differentiated), primary tumour (pancreas vs. other primary tumours), tumour burden (locoregional disease vs. disseminated), performance status (PS > 2), and treatment (surgery or chemotherapy).…”
Section: Discussionsupporting
confidence: 82%
“…However, assessing the degree of differentiation by histopathological criteria may be challenging and consensus is difficult to obtain even among expert pathologists [11,12]. To help discriminate between these two groups of neoplasms, studies have found mutations in TP53 or Rb1 and abnormal p53 and Rb1 immunohistochemical staining, as well as KRAS and BRAF mutations, to be a feature of NEC; whereas immunohistochemical loss of DAXX/ATRX, mutations in MEN1 and immunohistochemical expression of CgA and SSTR-2a is more frequently found in pancreatic NET G3 [7,8,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…One explanation for this difference between somatostatin receptor imaging and PSMA imaging may be the physiopathologic mechanism of tracer uptake. There is an inverse association between somatostatin receptor type 2A (SSTR2A) with the Ki-67 index, and SSTR2A is highly expressed in G1 and G2 neuroendocrine tumors but is significantly less abundant in neuroendocrine carcinomas (G3) (17); thus, higher expression of SSTR2A is correlated with lower grade of the neuroendocrine tumor. In contrast, the amount of PSMA expression is directly correlated with metastases, androgen independence, and progression of PC (18).…”
Section: Discussionmentioning
confidence: 99%
“…This hallmark is useful during designing diagnostic methods and modifying of cancer therapy. Overexpression of SSTRs has been found in well-differentiated neuroendocrine gastrointestinal neoplasms (GEP-NEN) so far [72]. Over 80% of GEP-NEN in the first and second stages of development expresses somatostatin receptors, especially SSTR2a [72].…”
Section: Sstrs In the Pathologies Of The Nervous Systemmentioning
confidence: 99%
“…Overexpression of SSTRs has been found in well-differentiated neuroendocrine gastrointestinal neoplasms (GEP-NEN) so far [72]. Over 80% of GEP-NEN in the first and second stages of development expresses somatostatin receptors, especially SSTR2a [72]. The results of studies of the SSTRs expression in glial tumors are inconclusive and the researchers are primarily focused on the expression of SSTR2 in high-grade tumors.…”
Section: Sstrs In the Pathologies Of The Nervous Systemmentioning
confidence: 99%